IMPLEMENTASI KONSEP KEBEBASAN TERHADAP KEMANDIRIAN ANAK USIA 5 - 6 TAHUN DALAM PERSEPEKTIF ISLAM DI RA DAARUL MAHDI PASARKEMIS TANGERANG - Fitri Pertiwi Pertiwi; Naila Attamimi (JECIES: Journal of Early Childhood Islamic Education Study, 2022)
The purpose of this study was to analyze the implementation of the concept of freedom and its influence on children's independence and related to the Islamic perspective at RA Daarul Mahdi. This research is a quantitative descriptive study, because the phenomena that occur can be classified, concrete, observable, measurable, and the relationship between symptoms is causal. The quantitative descriptive research approach is intended to examine the implementation of freedom and its effect on children's independence from an Islamic perspective. The results of this study Shows that parents have a role in developing children's independence. Based on the results of correlation calculations with product moment analysis obtained rxy of 0.71, there is a positive correlation and implied a strong correlation coefficient between the concept of freedom (variable X) and children's independence (variable Y). From the results of the calculation of the coefficient of determination obtained a value of 50.41%. Thus, the contribution of the concept of freedom to children's independence is 50.41% and this means that it is influenced by other factors, such as environmental factors.